(untitled) (Journal of the College of Languages (JCL), 2016)
This study aims at discussing how gender differences might affect communication among people. For this purpose, several TV interviews are selected and examined on the discourse level. Developing a model of analysis ,is found that certain linguistics have been used by male speakers ,whereas different aspects have been utilized my female speakers like deictic expressions and lexical items of emotion and delicacy .